Conversations with Interpreter Educators : Exploring Best Practices - Monikowski, Christine (Book collections on Project MUSE., 2017)
"Sign language interpreter education is a relatively young field that is moving toward more theory-based and research-oriented approaches. The concept of sharing research, which is strongly encouraged in this academic community, inspired Christine Monikowski to develop a volume that collects and distills the best teaching practices of leading academics in the interpreting field. In Conversations with Interpreter Educators, Monikowski assembles a group of 17 professors in the field of sign language interpretation. Through individual interviews conducted via Skype, Monikowski engages them in informal conversations about their teaching experiences and the professional publications that have influenced their teaching philosophies. She guides each conversation by asking these experts to share a scholarly publication that they assign to their students. They discuss the merits of the text and its role in the classroom, which serves to highlight the varying goals each professor sets for students. The complexity of the interpreting task, self-reflection, critical thinking, linguistics, backchannel feedback, and cultural understanding are a sampling of topics explored in these exchanges. Engaging and accessible, Monikowski's conversations offer evidence-based practices that will inform and inspire her fellow educators"--